Strategi Pengembangan Ruang Terbuka Hijau Privat Berbasis Wisata Bunga di Malino - Ainun Khusnuzhzhan; Shirly Wunas; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
Malino is one of the tourist destinations known as the City of Flowers located in Gowa Regency. Research on private Green Open Space (RTH) that supports the Malino tourist area, analyzes infrastructure supporting flower tourism in private RTH, and develops a strategy for developing interest-based private RTH. Data collection methods used were observation, interviews, collection and study of literature. The analytical method used is descriptive qualitative analysis, quantitative analysis, comparative analysis, and SWOT analysis. The results of this study are, the percentage of houses without public open space is 34% while the shape of the interest in green open space is determined by the horizontal shape. Furthermore, the URL infrastructure is sufficient to support trade, clean air, public transportation, and others. As a strategy to develop Malino as the City of Flowers, it is by utilizing the ideal land area of ​​8-10% as Private Green Space, increasing accessibility to tourist sites, and increasing the type of flower vegetation, from various scents, clouds and shapes.